Transgenic nonhuman primates for neurodegenerative diseases - Chan Anthony WS (BMC, 2004)
Abstract Animal models that represent human diseases constitute an important tool in understanding the pathogenesis of the diseases, and in developing effective therapies. Neurodegenerative diseases are complex disorders involving neuropathologic and psychiatric alterations. Although transgenic and knock-in mouse models of Alzheimer's disease, (AD), Parkinson's disease (PD) and Huntington's disease (HD) have been created, limited representation in clinical aspects has been recognized and the rodent models lack true neurodegeneration. Chemical induction of HD and PD in nonhuman primates (NHP) has been reported, however, the role of intrinsic genetic factors in the development of the diseases is indeterminable. Nonhuman primates closely parallel humans with regard to genetic, neuroanatomic, and cognitive/behavioral characteristics. Accordingly, the development of NHP models for neurodegenerative diseases holds greater promise for success in the discovery of diagnoses, treatments, and cures than approaches using other animal species. Therefore, a transgenic NHP carrying a mutant gene similar to that of patients will help to clarify our understanding of disease onset and progression. Additionally, monitoring disease onset and development in the transgenic NHP by high resolution brain imaging technology such as MRI, and behavioral and cognitive testing can all be carried out simultaneously in the NHP but not in other animal models. Moreover, because of the similarity in motor repertoire between NHPs and humans, it will also be possible to compare the neurologic syndrome observed in the NHP model to that in patients. Understanding the correlation between genetic defects and physiologic changes (e.g. oxidative damage) will lead to a better understanding of disease progression and the development of patient treatments, medications and preventive approaches for high risk individuals. The impact of the transgenic NHP model in understanding the role which genetic disorders play in the development of efficacious interventions and medications is foreseeable.